IUTAM Symposium on Solver-Coupling and Co-Simulation : proceedings of the IUTAM Symposium on Solver-Coupling and Co-Simulation, Darmstadt, Germany, September 18-20 2017 /: proceedings of the IUTAM Symposium on Solver-Coupling and Co-Simulation, Darmstadt, Germany, September 18-20 2017. ([2019]) - Unknown
No abstract available